Managing Teachers’ Cultural and Leadership Diversities for Service Delivery in Public Secondary Schools in Rivers State - Godwins, M.; Abraham, N. M.; Nwogu, U. J. (Advances in Social Sciences Research Journal, 2019)
The study examined the management of teachers’ cultural and leadership diversities for service delivery in public secondary schools in Rivers State. The research design was the descriptive survey. Two research questions and two hypotheses guided the study. Weighted mean score, standard deviation, and criterion mean were used to answer the research questions while z-test was used to test the null hypotheses at 0.05 level of significance. Theory X and Y propounded by Douglas McGregor in 1960, and the Need Achievement theory propounded by David C. McClelland in 1961 were the theoretical frameworks for the study. The population of the study included all 268 principals in all 268 public secondary schools in Rivers State. There were 153 male and 115 female principals, and, 62 urban and 206 rural secondary school principals. The sample for the study was 160 principals from the 268 public secondary school principals in Rivers State. This sample represented 60% of the population. The sampling technique adopted for the study was the proportionate stratified random sampling technique. The instrument for data collection was a self-designed questionnaire titled ‘Management of Teachers’ Diversities for Service Delivery Questionnaire’ (MTDSDQ). The questionnaire had 10 items. The reliability coefficient of the instrument was determine through Crombach alpha statistics. The reliability coefficient obtained was 0.81. The findings of the study revealed that the respondents agreed that the ways cultural diversity existing amongst public secondary school teachers is managed for service delivery in Rivers State include; teachers are asked not to speak their vernacular during general meetings held in the school, teachers are used as resource persons to help teach topics that are related to cultural diversities, teachers are allowed to form informal groups that is based on their different ethnic affiliations, there is no cultural discrimination in the way responsibilities are assigned to teachers and a deliberate effort is made to ensure that every ethnic group is represented in school committees. Findings also revealed that equal representation in committees, democracy in selections, are some of the ways of managing diversities arising from leadership. It was recommended that the government should organize annual inter-public-secondary-school teachers’ talent competition where prizes will be given to teachers who emerge winners and special incentives should be given to those who make significant contributions toward service delivery through the use of their cultural and leadership diversities.